'Moving on and feeling good': a feasibility study to explore the lifestyle behaviours of young adults with intellectual disabilities as they transition from school to adulthood—a study protocol. Issue 1 (December 2016) - Mitchell, Fiona; Jahoda, Andrew; Hankey, Catherine; Matthews, Lynsay; Murray, Heather; Melville, Craig
Abstract Background The transition from adolescence to adulthood is a 'high-risk' period for weight gain in the general population. There is speculation that this may also be a risk period for adults with intellectual disabilities; however, there has been no research which has monitored change in health indicators. Since adults with intellectual disabilities have higher rates of obesity and engage in more sedentary behaviour and less physical activity than the general population, there is a need to understand more about the lifestyle behaviours of this population during the transition to adulthood. This protocol paper will provide details of themoving on and feeling good feasibility study, designed for young people with intellectual disabilities. Methods/design A multi-point recruitment strategy will be used to recruit 30 participants with a mild-moderate level of intellectual disability. The aim of the feasibility study is to examine the feasibility of recruitment, participant retention and the measurement of relevant health behaviour outcomes. The study will assess the feasibility of monitoring weight, diet and physical activity levels in adolescents over a 12-month transitional period from school to adult life. This mixed method study will provide insight into the lives of young people with intellectual disabilities and will examine the use of Walker et al.'s social-ecological approach to promote self-determination specific to lifestyle behaviours, during this transition period. Baseline data will be collected during the final year of school, with follow-up data collection at 6 and 12 months. Anthropometric (weight, height, waist and hip circumference), objective physical activity measures (7-day accelerometer wear) and dietary and choice measures will be collected at each time point to assess the feasibility of measuring diet patterns, food frequency, physical activity and BMI. Furthermore, ten participants will be selected for short semi-structured scoping interviews at baseline and 12-month follow-up, to gain information on psychological, social and environmental factors which might affect behaviour change. Discussion The outcomes from the feasibility study will aid the development and piloting of a sufficiently powered randomised controlled trial. This would allow us to evaluate the effectiveness and sustainability of a lifestyle behaviour intervention, over a 5-year transition period.